Oil and gas in the Soviet Arctic - Armstrong, Terence (Polar Record, 1963)
Oil has been known in one locality of the Soviet Arctic since the second half of the seventeenth century (Probst, 1957). This is the deposit in the Ukhta region of Komi ASSR, known now as the Timano-Pechorskaya petroliferous province. Occasional attempts were made to obtain it, but intensive exploration started only in 1929, and significant exploitation in 1935. The oil is Devonian, aiid some of it is highly viscous. This led to development of a special mining technique for obtaining the oil, the extra cost being justified on the grounds that heavy oil of this type is particularly suitable for certain uses in the north. The refinery is at Ukhta itself, on the Pechora railway (Shishkin, 1959). Output figures have not been released, but are believed to have reached 1200 000 metric tons a year during World War II, but to have dropped in 1950 to 800 000 and in 1955 to 553 000 (Hassmann, 1953; Hodgkins, 1961). In the post-war period natural gas production was encouraged and it reached in 1960 about 1100 million m. per year (Rochev, 1961).